Inactivation of Escherichia coli in water by TiO2-assisted disinfection using solar light - Rodrigues,Cecília P. (2007)
TiO2-assisted heterogeneous photocatalysis and photolysis were evaluated for the disinfection of water samples using a glass reactor with immobilized TiO2 (catalyst), solar light and E. coli as an indicator microorganism of the efficiency of disinfection. Parameters such as color and turbidity of the water, level of coliform bacteria (by the Colilert® method), inclination angle of the solar reactor, solar light intensity, flow rate and retention time were controlled during the experiments. Two different operational modes were used for the solar reactor: single pass mode and recirculation mode. First, synthetic water was used in the disinfection tests as a model system; second, tests were conducted using natural samples specifically groundwater collected from a lake and a well. In bacterial suspensions in synthetic water in the absence of color and turbidity, heterogeneous photocatalysis was responsible for the reduction of approximately 100% of the initial concentration of E. coli. Only a 56.5% reduction was obtained by photolysis during the same solution recirculation time, which indicated a better efficiency using the catalyst. From the natural samples, total inactivation was not achieved in the studied cases. However, photocatalysis using TiO2/solar light was shown to be quantitatively efficient in the destruction of the total coliforms in water, reaching values up to around 80% inactivation in natural waters with initial levels of total coliforms ranging from 16.6 to 22.2´10³ MPN per 100 mL.